2015
DOI: 10.3389/fnbot.2015.00011
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic plasticity in a recurrent neural network for versatile and adaptive behaviors of a walking robot

Abstract: Walking animals, like insects, with little neural computing can effectively perform complex behaviors. For example, they can walk around their environment, escape from corners/deadlocks, and avoid or climb over obstacles. While performing all these behaviors, they can also adapt their movements to deal with an unknown situation. As a consequence, they successfully navigate through their complex environment. The versatile and adaptive abilities are the result of an integration of several ingredients embedded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…Manoonpong and his colleagues developed a series of modular neural CPG-based locomotion control for legged robots (Manoonpong et al, 2008 , 2013 ; Steingrube et al, 2010 ; Goldschmidt et al, 2014 ; Xiong et al, 2014 , 2015 ; Dasgupta et al, 2015 ; Grinke et al, 2015 ). They showed that using this control approach leads to adaptive interlimb coordination that allows the robots to deal with complex environments, such as walking over difficult terrain (Steingrube et al, 2010 ; Manoonpong et al, 2013 ; Goldschmidt et al, 2014 ; Xiong et al, 2014 , 2015 ; Dasgupta et al, 2015 ) and avoiding obstacles in an unknown cluttered area (Manoonpong et al, 2008 ; Grinke et al, 2015 ), as observed in insects. For example, they implemented modular neural control with an adaptive chaotic CPG-based network and sensory feedback on a hexapod robot (Figures 4A,B ; Steingrube et al, 2010 ).…”
Section: Adaptive Interlimb Coordination In Animals and Robotsmentioning
confidence: 99%
See 3 more Smart Citations
“…Manoonpong and his colleagues developed a series of modular neural CPG-based locomotion control for legged robots (Manoonpong et al, 2008 , 2013 ; Steingrube et al, 2010 ; Goldschmidt et al, 2014 ; Xiong et al, 2014 , 2015 ; Dasgupta et al, 2015 ; Grinke et al, 2015 ). They showed that using this control approach leads to adaptive interlimb coordination that allows the robots to deal with complex environments, such as walking over difficult terrain (Steingrube et al, 2010 ; Manoonpong et al, 2013 ; Goldschmidt et al, 2014 ; Xiong et al, 2014 , 2015 ; Dasgupta et al, 2015 ) and avoiding obstacles in an unknown cluttered area (Manoonpong et al, 2008 ; Grinke et al, 2015 ), as observed in insects. For example, they implemented modular neural control with an adaptive chaotic CPG-based network and sensory feedback on a hexapod robot (Figures 4A,B ; Steingrube et al, 2010 ).…”
Section: Adaptive Interlimb Coordination In Animals and Robotsmentioning
confidence: 99%
“…The robot efficiently walked on different surfaces including sponge, gravel, fine gravel, and grass. For adaptation to the avoidance of obstacles in a cluttered environment, an adaptive neural sensory processing network with synaptic plasticity was introduced to the modular neural control (Grinke et al, 2015 ). The adaptive processing network could drive different turning behaviors with short-term robot memory.…”
Section: Adaptive Interlimb Coordination In Animals and Robotsmentioning
confidence: 99%
See 2 more Smart Citations
“…Engineers have not developed any device with odor detection capabilities comparable to those of canines. Furthermore, some animals can traverse a variety of terrain types more efficiently than electromechanical robots or humans (Grinke et al, 2015 ); for instance, engineers have not developed a micro air vehicle with flight abilities comparable to those of pigeons. Animals could be employed to conduct search and rescue missions more efficiently than electromechanical robots if they could be controlled.…”
Section: Introductionmentioning
confidence: 99%